2010
DOI: 10.1002/polb.21850
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation effect of cyclodextrin inclusion complexes on the crystallization of isotactic poly(1‐butene)

Abstract: The β‐cyclodextrin (β‐CD) and γ‐cyclodextrin (γ‐CD) inclusion complexes (ICs) with four kinds of polyolefin were prepared. The crystallization behavior of isotactic poly(1‐butene) (iPB‐1) blended with these CDs and ICs was investigated by differential scanning calorimetry, polarized optical microscopy, and wide‐angle X‐ray diffraction. The iPB‐1 blended with the ICs was found to exhibit higher crystallization temperature (TC), smaller spherulites, and faster crystallization rate than neat iPB‐1. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, with the addition of PCLIC, the number of nuclei increased markedly and the average diameter of the spherulites was reduced, indicating superior nucleating activity, which is consistent with the DSC analysis. The above results are consistent with the phenomenon described by Li et al, 23 where the ICs formed with the polymer having guest molecules with a higher T C will have a higher nucleation effect than the one with the polymer having lower T C guest molecules. Furthermore, the ICs with guest molecules having a higher molecular weight will have a higher nucleation effect than the ones with lower molecular weight guest molecules.…”
Section: Isothermal Crystallization Behavior Of Pba Containing Nuclea...supporting
confidence: 92%
See 1 more Smart Citation
“…However, with the addition of PCLIC, the number of nuclei increased markedly and the average diameter of the spherulites was reduced, indicating superior nucleating activity, which is consistent with the DSC analysis. The above results are consistent with the phenomenon described by Li et al, 23 where the ICs formed with the polymer having guest molecules with a higher T C will have a higher nucleation effect than the one with the polymer having lower T C guest molecules. Furthermore, the ICs with guest molecules having a higher molecular weight will have a higher nucleation effect than the ones with lower molecular weight guest molecules.…”
Section: Isothermal Crystallization Behavior Of Pba Containing Nuclea...supporting
confidence: 92%
“…It was recently reported that the addition of CD and its inclusion complex to biodegradable polymers can effectively enhance the crystallization rate of the polymer. [20][21][22][23] The reduction of T C and enhancement of the crystallization rate may be important for increasing the thermodynamic stability of the polymer. Such enhancement by a-CD leads to an increase in the glass transition temperature of the polymer in the complexed state.…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been tried to obtain smart nanocomposite with different properties, like piezoresistivity (sensors) and conductivity (electrical connection). The most recent researches proved that adding carbon nanoparticles (such as graphene nano platelets (GNP), or carbon black (CB), or carbon nanotubes (CNT)) to commercial polymer composites can provide an improvement of the mechanical behaviors [1][2][3], thermal conductivity [4,5], electric conductivity [6][7][8][9], and piezoresistive behavior [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] At present, a large number of potential nucleating agents have been reported in the literature, which include inorganic nucleating agents, such as nanoclays, [18,19] layered metal phosphonates, [20] and organic nucleating agents such as amide derivatives, [21,22] hydrazide compounds, [23] and supramolecules. [24] So that the problem of poor compatibility with the polymeric matrix can be overcome, the choice of an appropriate organic nucleating agent is crucial. In recent years, cyclodextrins (CDs) and their inclusion complexes (ICs) have been found to effectively enhance the crystallization rates of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the solid‐state morphology of sheared polymers is also altered, which improves the physical and optical properties of the materials, while retaining their inherent useful properties . At present, a large number of potential nucleating agents have been reported in the literature, which include inorganic nucleating agents, such as nanoclays, layered metal phosphonates, and organic nucleating agents such as amide derivatives, hydrazide compounds, and supramolecules …”
Section: Introductionmentioning
confidence: 99%